Использование учебной деловой игры на уроках информатики - Искакова, Г.К. (My University, 2016)
Interest in studying of computer science in many aspects depends on how the lessons pass. Even at the best lessons the element of obligation constrains development of creative activity, and, as a result, enthusiasm for a subject. Therefore it is very important to take care of that each student worked at lessons, actively and with enthusiasm, and to use it as a starting point for emergence and development of inquisitiveness, cognitive interest, creative thinking.
Keywords: business game; computer technologies; creative thinking